O Número De Ouro Na Educação Básica - Silva, Alessandro Jose Da [UNIFESP] (2018)
This Work Presents A Study On The Golden Number, Contemplating Its History, Definition And Some Of Its Properties. Research About The Origin Of The Golden Number Indicates Close Connection With Large Architectural Works Such As The Pyramid Of Egypt And The Parthenon, Revealing The Connection With The Golden Number And The Fibonacci Sequence. It Presents The Algebraic And Geometric Methods Of Obtaining The Segment, The Rectangle And The Golden Spiral Using The Ruler And Compass. It Displays That The Golden Number Manifests Itself In Nature, Architecture And In The Human Body. It Exhibits Activities Related To The Golden Number, Focused On Basic Education. It Points Out That The Subject Studied Reveals Itself As A Good Opportunity To Be Worked In The Classroom, Praising The Beauty Of Mathematics And Fostering Interdisciplinarity, Thus Awakening Students" Interest.